Prevalence of frailty in institutionalized elderly in the city of Rio Verde – Goiás (Research, Society and Development, 2022)
Objective: to determine the prevalence of frailty and associated factors in elderly people living in a long-term care facility. Method: cross-sectional descriptive study conducted with elderly residents in a long-term institution. The research was conducted through two questionnaires: a form for data collection regarding identification, sociodemographic and economic characteristics, and general health in the multidimensional assessment instrument for the elderly called Brazilian Functional Assessment Questionnaire (BOMFAQ) and Edmonton Frailty Scale, which assesses the level of frailty of elderly people. Results: 75 elderly were analyzed, among which 81,33% were considered frail. It was found that the age group from 60 to 79 years old, and retirees had a significantly relevant relationship with frailty. Conclusion: most of the elderly evaluated presented frailty, which is a syndrome of multidimensional character, impacts on the personal, family and social life of the elderly, it can be a precursor of functional decline, but because it can be identified early, it has potential for prevention and treatment of symptoms.